2014
DOI: 10.1186/1742-4690-11-s1-p17
|View full text |Cite
|
Sign up to set email alerts
|

Nation-wide epidemiological study in Japan on HTLV-1 associated myelopathy/tropical spastic paraparesis using HAM-net, a novel patient registration system

Abstract: Coler-Reilly et al.: Nationwide epidemiological study in Japan on HTLV-1 associated myelopathy/tropical spastic paraparesis using HAM-net, a novel patient registration system. Retrovirology 2014 11(Suppl 1):P17.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…While in the last 15 years, it became clear that HTLV-1infected individuals even without myelopathy had urinary symptoms and erectile dysfunction 22,23 ; no studies have evaluated intestinal complaints in such patients. In patients with HAM / TSP, the frequency of constipation was reported to be greater than 60 % 15,16 . It is known that intestinal dysfunction is common in patients with spinal cord injuries 24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While in the last 15 years, it became clear that HTLV-1infected individuals even without myelopathy had urinary symptoms and erectile dysfunction 22,23 ; no studies have evaluated intestinal complaints in such patients. In patients with HAM / TSP, the frequency of constipation was reported to be greater than 60 % 15,16 . It is known that intestinal dysfunction is common in patients with spinal cord injuries 24 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the occurrence of neurogenic bowel in individuals infected with HTLV-1 has been poorly studied. Constipation appeared the most frequent digestive tract symptom in HTLV-1 patients and two retrospective studies showed that it was present in 67 % and 78.2 % of patients with HAM / TSP 15,16 . These studies did not address the frequency of other bowel symptoms and did not use a seronegative control group to allow a more rigorous comparison.…”
Section: Introductionmentioning
confidence: 99%
“…Factors that affect the health and the quality of life in patients were highlighted at this meeting, such as HIV co-infection and physical inactivity. Nation-wide epidemiological studies with a novel patient registration system in Japan appears to be an important improvement (Coler-Reilly et al ), which is expected to evolve into an international system because of the relatively small number of HAM/TSP patients [ 42 ]. Three abstracts described familial clustering of HAM/TSP patients (Nozuma et al , Coler-Reilly et al , and Alvarez et al .)…”
Section: Introductionmentioning
confidence: 99%
“…Three abstracts described familial clustering of HAM/TSP patients (Nozuma et al , Coler-Reilly et al , and Alvarez et al .) [ 42 - 44 ]. Results from Nozuma et al and Coler-Reilly et al suggested positive clustering and lower age of onset [ 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation